ROLE OF THE ABSTRACT NAME IN THE SPEECH DEVELOPMENT OF A CHILD (ON THE BASIS OF A DIARY) (Proceedings of Southern Federal University. Philology, 2014)
The article studies the influence of the abstract name (AN) on the development of children’s speech. AN having a number of semantic features (absence of visual prototype valence on interpretant due to its mythological and cause dialogic, affects the child’s thinking and speech, shaping him as a person, and also affects the formation of the world picture, as it is formed by development of concepts. Functioning of the AN in the child’s speech reveals the mechanisms by which the child is learning the native language. The paper used the method of comparative analysis of the context, which allows to research the semantic specificity of AN in the gender aspect, namely to investigate the presence / absence of differences in the methods of perception and evaluation of heterosexual children of abstract entities, standing behind the AN. Functioning of abstract names in children’s speech is a little-studied area in ontolinguistics, but is of particular interest to the researcher, as demonstrates the features of development of the child the mother tongue.Key words: abstract name, baby talk, communication strategy, ontolinguistics